2019
DOI: 10.1016/j.cep.2019.107681
|View full text |Cite
|
Sign up to set email alerts
|

Influence of high-intensity ultrasound application on the kinetics of sugar release from acid suspensions of artichoke (Cynara scolymus) biomass

Abstract: The study of sugar release kinetics is an essential step prior to developing new technologies for applying in the bioethanol industry. To this end, the kinetics of reducing and total sugar release (extraction/hydrolysis) from artichoke waste were obtained in different conditions to evaluate the solubility of free sugars from raw matter and the hydrolysis of larger chain molecules separately. Thus, experiments of extraction with water (WE), hydrolysis (HY) in acid solutions and a conventional industrial hydroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
0
13
0
2
Order By: Relevance
“…For sugars, Polachini et al. (2019) observed a positive effect of ultrasound‐assisted extraction time, with an increase of ~ 13% in the interval of 15–60 min. As described by Setyaningsih, Saputro, Carrera, and Palma (2019), the effects of ultrasound cavitation enhanced the permeability of the matrix tissues with the increase of processing duration, leading to more release of analytes into the solvent from the different portions of matrix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For sugars, Polachini et al. (2019) observed a positive effect of ultrasound‐assisted extraction time, with an increase of ~ 13% in the interval of 15–60 min. As described by Setyaningsih, Saputro, Carrera, and Palma (2019), the effects of ultrasound cavitation enhanced the permeability of the matrix tissues with the increase of processing duration, leading to more release of analytes into the solvent from the different portions of matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The efficiency of ultrasound‐assisted extraction (UAE) to the removal of phenolic compounds from food materials was reported in various works, such as: mandarin peel (Nipornram, Tochampa, Rattanatraiwong, & Singanusong, 2018), black and purple rice bran (Das, Goud, & Das, 2017), pomegranate peel (Machado et al., 2019; Sharayei, Azarpazhooh, Zomorodi, & Ramaswamy, 2019), teff grains (Viell et al., 2020), and Brazilian hop (Almeida et al, 2019). At same time, UAE efficacy in the extraction of soluble sugars was observed for defatted soybean flakes (Karki et al, 2010), banana (Rayo‐Mendez, Gómez, & Tadini, 2019), and artichoke biomass (Polachini, Mulet, Telis‐Romero, & Cárcel, 2019). However, it was not found studies about the use of UAE, specially under maximized conditions, to extracts phenolic compounds or soluble sugars, from the by‐product of heart‐of‐palm (stem portion).…”
Section: Introductionmentioning
confidence: 86%
“…La mayor concentración de DPPH se obtuvo con diámetros de partícula entre 0.85-1.00 mm Jiménez Islas et al (2012) showed the effect of the concentration of the acid used in the hydrolysis processes and mentioned that there can be an interference due to the variation in the size of particles of the material, mainly its interaction between the surface area and the acid attack towards the particles. To improve sugars extraction by thermal hydrolysis processes, a lower particles size supposes lower changes in the adhesion forces among particles of different sizes (Polachini et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Jiménez Islas et al (2012) mostraron el efecto de la concentración del ácido empleado en los procesos de hidrólisis y mencionan que la interferencia se puede dar debido a la variación en el tamaño de partícula del material, principalmente su interacción entre el área superficial y el ataque ácido hacia las partículas. Para mejorar la extracción de los azúcares por procesos de termo-hidrólisis, un menor tamaño de partícula supondrá menores cambios en las fuerzas de adhesión entre partículas de diferentes tamaños(Polachini et al, 2019).Análisis experimental del tratamiento de hidrólisis térmicaLos niveles evaluados experimentalmente para poder estudiar el proceso de hidrólisis térmica presentaron perfiles de calentamiento y enfriamiento con tiempos de 13±2 min y 22±2 min respectivamente. La Tabla 3 muestra los análisis de varianza efectuados para los azúcares reductores obtenidos de los tratamientos derivados del diseño ortogonal L-9.…”
unclassified
“…Different studies have used vacuum pulsing (Martins et al, 2019), ohmic heating (Coelho et al, 2019), electrodialysis (Xue et al, 2018), high pressure (Shinwari and Rao, 2018), microwave (Leonelli and Mason, 2010), and high-power ultrasound (Polachini et al, 2019;Goula et al, 2017), in order to accelerate mass transfer rates. Ultrasound is a promising emerging technology in the food processing industry, as it is innovative, achieving important results generally complementary to classical techniques, such as salting (Sharma and Dash, 2019).…”
Section: Introductionmentioning
confidence: 99%